Loop Diuretics in Acute Kidney Injury Prevention, Therapy, and Risk Stratification - Daniel Patschan; Susann Patschan; Ivo Buschmann; Oliver Ritter (Karger Publishers, 2019)
Background: Loop diuretics (LD) are widely used in emergency and intensive care medicine. Summary: The substances increase the clearance of electrolytes and water; thus, they allow us to control hypervolemia and to prevent patients from pulmonary edema. LD are also frequently applied to patients with an acute decrease in glomerular filtration rate, namely, acute kidney injury (AKI). Nevertheless, volume depletion may be associated with reduced renal perfusion and possibly slower restitution or even aggravation of kidney dysfunction. Several trials on the preventive or therapeutic efficacy of LD have been published since the early 1970s. Our review article is intended to summarize the most important references related to this topic. In addition, we discuss the diagnostic value of the so-called furosemide stress test. The currently available data indicate that LD may act in a beneficial manner as long as euvolemia is maintained (matched hydration). Key Massages: LD are not beneficial for AKI treatment if kidney-related endpoints are considered. In certain situations, AKI prevention with LD can be associated with favorable outcomes as long as euvolemia is maintained. LD can help to identify AKI subjects at a higher risk of AKI progression, but the exact clinical consequences need to be determined.